2019
DOI: 10.1111/phn.12646
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Integrated Behavioral Model to oral self‐care behavior of community‐dwelling middle‐aged and older people in Taiwan

Abstract: Objectives: This study evaluated the Integrated Behavioral Model and examined oral self-care behavior of community-dwelling middle-aged and older people. Design: A cross-sectional design was used. Sample: Purposive sampling was employed to recruit middle and older age community-dwelling individuals, with research locations in public health centers in northern Taiwan. Measurements: Structured questionnaires comprised: participant demographics, oral health literacy, oral self-care attitude, self-efficacy, intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We speculate at least several reasons that might account for the disparities reported by our Taichung sample: First, medical resources were insufficient for the current Taiwanese older adults during their childhood and youth compared with the younger cohorts in Taiwan. Second, due to insufficient oral health literacy (Ho et al, 2019; Hsu et al, 2013), most of the older adults in Taiwan often reported poor oral hygiene perceptions and behaviors (Hsu et al, 2013; Lin et al, 2016; Wang et al, 2013). As a result, they tended to suffer from serious oral health problems and had poor self-rated oral health.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate at least several reasons that might account for the disparities reported by our Taichung sample: First, medical resources were insufficient for the current Taiwanese older adults during their childhood and youth compared with the younger cohorts in Taiwan. Second, due to insufficient oral health literacy (Ho et al, 2019; Hsu et al, 2013), most of the older adults in Taiwan often reported poor oral hygiene perceptions and behaviors (Hsu et al, 2013; Lin et al, 2016; Wang et al, 2013). As a result, they tended to suffer from serious oral health problems and had poor self-rated oral health.…”
Section: Discussionmentioning
confidence: 99%
“…In public health policies, a growing body of evidence indicated that the oral health literacy is the key to understand people’ awareness as well as the determinants of oral health (Atchison et al, ; Ho, Chang, et al, ; Sistani et al, ; Vyas et al, ). The results of this study should lead to an extensive survey of OHL in the Mandarin population, which will allow us to study OHL predictors in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, lower educational level, lower economic status, unemployment, and wearing of removable dentures are other risk factors for inadequate OHL (Ho, Liu, et al, ; Naghibi Sistani, Montazeri, Yazdani, & Murtomaa, ; Vyas, Nagarajappa, Dasar, & Mishra, ). Culturally specific determinants of oral health behaviors among people in Taiwan include OHL, oral self‐care attitude, self‐efficacy, and intention, and significant others’ perceptions and beliefs as well as environmental constraints (Ho, Chang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, researchers admitted that caregivers in communities consistently played an important role by enhancing oral health knowledge, maintaining positive attitudes, increasing older persons' ability to perform oral self-care, and enhancing oral self-care awareness [28]. Currently, there are assessment scales focusing on older persons' or periodontal patients' oral health status in China, usually using oral health self-efficacy as a sensitive indicator [29,30].…”
Section: Plos Onementioning
confidence: 99%